2001
DOI: 10.1177/03635465010290011501
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Anthropometric Measurements, Strength, Anterior Cruciate Ligament Size, and Intercondylar Notch Characteristics to Sex Differences in Anterior Cruciate Ligament Tear Rates

Abstract: We performed a prospective study based on the hypothesis that physiologic differences exist between men and women in strength after adjustments for body weight; that the size of the anterior cruciate ligament is proportionate to the strength of its antagonists, the quadriceps muscles; and that women have a relatively small anterior cruciate ligament, thus predisposing them to a disproportionate number of anterior cruciate ligament injuries. One hundred matched high school basketball players, 50 male and 50 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
292
6
20

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(333 citation statements)
references
References 49 publications
15
292
6
20
Order By: Relevance
“…While there is still disagreement in the literature as to whether variations in notch geometry related to differences in gender or limb dominance, play a contributing role in ACL injuries, we did not find a difference in NWI with respect to gender, involved side, mechanism of injury or type of sport engaged in at the time of injury [7,12,13,18,21,22].…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…While there is still disagreement in the literature as to whether variations in notch geometry related to differences in gender or limb dominance, play a contributing role in ACL injuries, we did not find a difference in NWI with respect to gender, involved side, mechanism of injury or type of sport engaged in at the time of injury [7,12,13,18,21,22].…”
Section: Discussioncontrasting
confidence: 87%
“…This difference may be caused by different imaging techniques used for the evaluation of NWI. Two studies measuring NWI using MRI [8,21] have shown much higher values for normal adult populations than values reported in radiographic studies [2][3][4][5][6][7]20].…”
Section: Discussionmentioning
confidence: 90%
“…The PTS of the bony tibial plateaus frequently is mentioned for its association to noncontact ACL injury [3,18,40,45]. It is defined by a tangent line to the respective tibial plateau and a line perpendicular to the longitudinal axis (LA) of the tibial bone that averages 10°(± 3°) on radiographs [9,13,16,19].…”
Section: Introductionmentioning
confidence: 99%
“…The findings then were compared with published data from human knees. Results Female pigs had smaller bicondylar widths (2.9 mm, ratio = 0.93, effect size = À1.5) and intercondylar notches (width: 2.0 mm, ratio = 0.79, effect size = À2.8; area: 30.8 mm 2 , ratio = 0.76, effect size = 2.1; index: 0.4, ratio = 0.84, effect size = À2.0), steeper lateral tibial slope (4.3°, ratio = 1.13, effect size = 1.1), smaller ACL (length: 2.7 mm, ratio = 0.91, effect size = 1.1; area: 6.8 mm 2 , ratio = 0.74, effect size = À1.5; volume: 266.2 mm 3 , ratio = 0.68, effect size = À1.5), thinner medial femoral cartilage (0.4 mm, ratio = 0.8, effect size = À1.1), lower ACL yield load (275 N, ratio = 0.81, effect size = À1.1), and greater AP knee laxity at 30°( 0.7 mm, ratio = 1.32, effect size = 1.1) and 90°(0.5 mm, ratio = 1.24, effect size = 1.1) flexion compared with their male counterparts. These differences were significant for all parameters (p B 0.04).…”
mentioning
confidence: 98%